The ten-year probability of fractures with the FRAX tool: which threshold for intervention to be used and how? - O. M. Lesnyak; E. N. Gladkova; O. B. Ershova; I. A. Skripnikova; O. N. Anoshenkova; Yu. R. Akhverdyan; K. Yu. Belova; I. B. Belousova; E. V. Bolshakova; A. V. Dreval; B. V. Zavodovsky; M. V. Ilyin; et al. (Научно-практическая ревматология)
Objective: to analyze the clinical and organizational feasibility of using different intervention thresholds for the Russian population.Subjects and methods. The probability of fractures using the Russian FRAX model was calculated on a sample of 3,866 postmenopausal female residents from 6 cities of the Russian Federation. Different intervention thresholds, including fixed (20% for major fractures and 3% for hip fractures), age-dependent (European and Russian) ones, as well as alternative models, were analyzed. The proportion of women to be treated was estimated using different intervention thresholds.Results and discussion. The analysis of the effectiveness of the thresholds showed that the European threshold was the least appropriate one for the formed sample, since more than half (53.6%) of the women to be treated using the threshold, while the vast majority (90%) of the patients were in the younger age groups (50—54 years). There were very similar results of the effectiveness analysis of the fixed threshold (according to the USA National Osteoporosis Foundation — NOF) recommendations and that of the age-dependent threshold for Russia (in the context of the national clinical recommendations). Using the NOF approach in our sample could identify 47.8% of the postmenopausal women to be treated for osteoporosis. Their proportion rose from 29.6% of the patients aged 50—54 years to 80.6% of those aged 85 years and older. The alternative analyses of age-dependent thresholds showed great effectiveness when the fracture was considered not as a risk factor for future fractures, but as a clinical disease manifestation that was sufficient to recommend that the patient should be treated without FRAX counting. However, with their use, the proportion of older people to be treated remains not high enough. In this connection, there remains a need to search for the more adequate application of the existing intervention threshold or to develop a new, for example, hybrid variant of the age-dependent threshold.